Knowledge, attitude, and practice towards occupational burnout among doctors and nurses in intensive care unit - Lu, Xiahui; Li, Dawei; Luo, Hu; Wang, Lishan; Lou, Yan; Yu, Yanyan (Frontiers in Public Health, 2025)
BackgroundOccupational burnout is prevalent among doctors and nurses. This study aimed to investigate the knowledge, attitude, and practice (KAP) of ICU doctors and nurses regarding occupational burnout.MethodsA cross-sectional study was conducted between December 2023 and June 2024 at the Zhejiang Medical & Health Group Hangzhou Hospital in Zhejiang Province. Demographic information and KAP scores were collected through distributed questionnaires. Occupational burnout was measured by the Maslach Burnout Inventory-General Survey (MBI-GS).ResultsThis study included 105 doctors and 165 nurses, with an average age of 32.23 ± 7.38 years. Among all the participants, 6 (2.22%) reported no occupational burnout, 230 (85.19%) experienced moderate occupational burnout, and 34 (12.59%) reported severe occupational burnout. The mean knowledge, attitude, and practice scores were 9.64 ± 4.21 (possible range: 0–18), 29.01 ± 3.15 (possible range: 7–35), and 16.96 ± 4.29 (possible range: 6–30), respectively. Multivariate logistic regression revealed that a higher knowledge score was independently associated with more proactive practice (OR = 1.33, 95% CI: [1.18, 1.50], p < 0.001). Structural equation modeling showed that knowledge positively influenced both (β = 0.33, p < 0.001) and practice (β = 0.37, p < 0.001), while practice negatively impacted the MBI-GS (β = −0.92, p < 0.001).ConclusionMost ICU doctors and nurses exhibited moderate occupational burnout, with insufficient knowledge, positive attitude, and moderate practice toward occupational burnout. Implementing strategies to increase knowledge and promote active practical engagement is essential to effectively mitigate occupational burnout among ICU staff.